Disfemisme Ungkapan Umpatan pada Terjemahan Arab-Indonesia Cerpen “طبلية من السماء” Karya Yusuf Idris - Uswatun Khasanah; Moh Zawawi; Muhammad Zarnubi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This article examines the use of dysphemism in swear words in the translation of Yusuf Idris's short story “Thobaliyyah Min As-Sama'” into Herpin Nopiandi Khurosan's short story “Tray from Heaven”. Dysfeminism refers to the use of language that is designed to emphasize negative connotations and make a statement sound worse or harsher. This study aims to determine the form of swear word dysphemism in the Arabic-Indonesian translation of the short story “Thobaliyyah Min As-Sama'”, knowing the function of swear word dysphemism in the Arabic-Indonesian translation of the short story “Thobaliyyah Min As-Sama”. The theory used in this research is Allan and Burridge's theory of dysphemism. The method of this research is descriptive qualitative, with 2 data collection techniques, namely reading the entire contents of the short story and recording the data in accordance with the theory. Then the data were analyzed using the Miles and Huberman method, namely by collecting data, reducing data, presenting data, and conclusions. The results of this study show that there are some data that show the existence of dysphemism in swear words. Among them have functions, namely, to vent the speaker's emotions, to joke, to demean the listener, and to swear. This research makes an important contribution to the understanding of how dysphemisms are translated and how shifts in language can affect the meaning and emotional impact of literary texts. For future research, it is hoped that other researchers can explore the comparison of dysphemisms in various literary genres or in the context of translation between different languages.